Learning by doing with others. A study of children's learning in the frame of activity systems of rural communities - Rosemberg, Celia R. (2007)
This study analyses the process by which children from poor rural communities acquire knowledge and abilities involved in their communities activity systems. These systems are the interactive contexts in which children's language and cognitive development take place.